2008
DOI: 10.1097/brs.0b013e3181646ba1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome-Based Classification for Assessment of Thoracic Pedicular Screw Placement

Abstract: The literature shows consensus over high rates of pedicle screw misplacement, but low clinical complications, in the hands of the best of spine surgeons. The concept of acceptable screw placements and the outcome classification makes the pedicle screw assessment results correlate better with the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 19 publications
0
61
0
5
Order By: Relevance
“…We believe that pedicle screws with ACP with the screw tip in the vicinity of aorta need to be followed up with a suitable imaging modality, for example CT-angiography, to exclude the development of pseudoaneurysm. We believe that adopting the new grading system (based on whether the cortical violation is partial or total rather than measuring the misplacement in millimeters and regarding the screw misplacement of less than half screw diameter as ''acceptable'') is more practical and easy to perform for research purposes as well as in clinical practice as: (1) pedicle perforation of B2 mm (almost half screw diameter) is considered harmless [3]. (2) The pedicular width in the thoracic spine may be as small as 2.6 mm [13], which means that many pedicle screws are inclined for misplacement regardless of the skilfulness of the operating surgeon as screw diameter varies between 4.5 and 5.5 mm, and (3) avoiding measurements in millimeter and submillimeter reduces the influence of individual variations and avoids the inherent error of measurements when these are performed in the Picture Archiving and Communication System (PACS).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We believe that pedicle screws with ACP with the screw tip in the vicinity of aorta need to be followed up with a suitable imaging modality, for example CT-angiography, to exclude the development of pseudoaneurysm. We believe that adopting the new grading system (based on whether the cortical violation is partial or total rather than measuring the misplacement in millimeters and regarding the screw misplacement of less than half screw diameter as ''acceptable'') is more practical and easy to perform for research purposes as well as in clinical practice as: (1) pedicle perforation of B2 mm (almost half screw diameter) is considered harmless [3]. (2) The pedicular width in the thoracic spine may be as small as 2.6 mm [13], which means that many pedicle screws are inclined for misplacement regardless of the skilfulness of the operating surgeon as screw diameter varies between 4.5 and 5.5 mm, and (3) avoiding measurements in millimeter and submillimeter reduces the influence of individual variations and avoids the inherent error of measurements when these are performed in the Picture Archiving and Communication System (PACS).…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of misplacement reported in this study was 17%. Five of the studies dealing with assessment of pedicular screw placement in scoliosis showed a misplacement rate of 5.7, 50.7, 25, 29.1, and 18.5% [1,3,9,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations